The Correlation Between Self Control and Peer Social Support with Student Stress Levels During Online Learning in Pandemic Covid-19 - Evi Ni’matuzzakiyah (GLOBAL HEALTH SCIENCE GROUP, 2022)
Students are required to be able to develop themselves to the maximum in various problems. During the current pandemic, students are faced with the problem of online learning where the academic burden is not the same as when they did face-to-face learning before the pandemic. There are several problems that students complain about; family economic problems, unstable internet network problems, and the many assignments from lecturers that they have to complete. This causes them to feel bored and experience fatigue in participating in online learning. Objective: This study aims to determine the relationship between self-control and peer social support with stress level in Public Health STIKes Surya Global Yogyakarta students during online learning in COVID-19 pandemic. Method: The design of this study is a quantitative descriptive design with a cross sectional approach. The sample is 65 samples of students using purposive sampling. Data were analyzed using Chi square. Results: There is a significant correlation between self-control and the stress level with p = 0.003 < α = 0.05. Conclusions: there is also a significant correlation between peer social support and the stress level with p = 0.003 < = 0.05.